Tailored-Designed Ligands for Enantioselective Gold(I)-Catalyzed Activation of Alkynes - Mora, Pablo; Escofet, Imma; Echavarren, Antonio (Synlett, 2025)
In this article, we describe the work performed at our laboratories over the years on the design and applications of novel chiral ligands for the enantioselective gold(I)-catalyzed activation of alkynes, with a focus on the cycloisomerization and cycloaddition reactions of 1,6-enynes. The rationale behind the development of each ligand and the mode of enantioinduction are discussed.
Keywords: Chiral ligands; Enantioselective synthesis; Gold catalysis; Enynes; Alkynes